Facing Your Opponents: Social Identification and Information Feedback in Contests - Mago, Shakun D.; Samak, Anya C.; Sheremeta, Roman M. (The Journal of conflict resolution, 2016)
We experimentally investigate the effect of social identification and information feedback on individual behavior in contests. In all treatments, we find significant overexpenditure of effort relative to the standard theoretical predictions. Identifying subjects through photo display decreases wasteful effort. Providing information feedback about others' effort does not affect the aggregate effort, but it decreases the heterogeneity of effort and significantly affects the dynamics of individual behavior. A behavioral model that incorporates a nonmonetary utility of winning and relative payoff maximization explains significant overexpenditure of effort. It also suggests that decrease in ``social distance'' between group members through social identification promotes prosocial behavior and decreases overexpenditure of effort, while improved information feedback decreases the heterogeneity of effort.